Hyperreality and Fandom Capitalism: An Analysis of Day6’s Fandom Consumptive Behavior in Purchasing Merchandise as an Identity Construction - elsa ananda; Edi Nurwahyu Julianto; Ami Saptiyono (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah, Institut Agama Islam Sunan Giri Ponorogo, 2025)
He phenomenon of fanaticism communities (fandom) of K-POP in Indonesia is not merely related to music, but also involved merchandise comsumption practice that has symbolic meaning. This research aims to explore the role of hyperreality and fandom capitalism in constructing compsumtive behavior of DAY6’s fandom. This research located in Semarang, particularly through purchasing activity of DAY6 merchandise as the part of identity construction. This research using qualitative phenomenological approach through in-depth interview method toward DAY6’s fans who actively participate in the community and has high intensity of merchandise purchasing. The analysis is conduct through tematic analysis for identifed meaning pattern that appears from informan’s experience. The results show three key findings. First, merchandise plays a role as a simulation of the idol’s presence. Second, merchandise consumptions contributes to shape the identity of fans as “MY DAY”, the name of DAY6’s fandom. Third, merchandise ownership is related to social recognition within the DAY6 community. The research concludes that DAY6’S fans consumptive behavior cannot be viewed simply as an economic activity, but rather as a symbolic meaning that shapes emotional closeness, fandom identity, and social relations within fandom hyperreality and capitalism.